Analisis Kualitas Pelayanan PT Jasa Raharja dengan Metode Servqual - Hindarwati, Enny Noegraheni; Jayasari, Anintia (Binus Business Review, 2014)
In order to improve the image of insurance company, this study was done to find a picture of the accident victimâs satisfaction with the service of insurance company Jasa Raharja. Descriptive quantitative research was conducted with a population of accident victims. Data were taken with questionnaires by 80 respondents and data analysis used SERVQUAL. The results showed that the overall levels of accident victimâs satisfaction with the service of insurance company Jasa Raharja levels are disatisfied. This is evident from the value of the gap between perception and negative expectation. Dimensions of perceived service quality as dissatisfaction by the accident victims are the reliability, responsiveness, assurance, and empathy dimension. Result was obtained from this research gap between perception and expectation of service with a value of - 0.0284. Therefore, it is suggested to the insurance company Jasa Raharja to improve services to accident victims, especially dimensions unsatisfactory service for accident victims.